Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan - Muhammad Ras Muis; J Jufrizen; Muhammad Fahmi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2018)
This study aims to determine the effect of partial and simultaneous organizational culture and organizational commitment to the performance of employees. The population is the sum total of the object of research. The population in this study is all employees who exist in PT Pegadaian (Persero) Kanwil I - Medan, which amounts to 60 people. Due to the small number of employees in the company, this study did not use sampling. So the sample in this study is the total number of employees at PT Pegadaian (Persero) Kanwil I - Medan, which amounts to 60 people. Data collection techniques in this study is a list of questions (questioner), study documentation and interviews (interview). While the data analysis technique used is multiple linear regression, classical assumption test, t-test, and F test and determinant coefficient. The result of this research shows that there are positive and significant influence of organizational culture on performance, and there are positive influence and significant organizational culture and organizational commitment to employee performance.